A Framework for the Co-Design of an Integrated Mobile-Assisted Learning Environment for ESL Learners - Chuah, Kee Man; Muhammad Kamarul, Kabilan (Penerbit USM, 2025)
For more than a decade after the smartphone revolution achieved its global prominence, the use of mobile applications in language learning has almost become second nature to educators and learners. From e-dictionary to social network inspired language learning applications, it is safe to assume that mobile technology is impacting the way traditional language teaching is conducted in classrooms. Studies have reported various advantages of using mobile applications to support language teaching and learning, particularly in the context of English as a second or foreign language (ESL/EFL). These advantages can be grouped broadly into three scopes, that is, increasing authentic language learning opportunities (Chaya & Inpin, 2020; Godwin-Jones, 2011; Petersen & Markiewicz, 2008; Shadiev et al., 2020), supporting task-based language learning activities (Kukulska-Hulme & Viberg, 2018; Ma, 2017; Sweeney & Moore, 2012; Xue, 2020), and monitoring progress through formative assessments (Cabrera-Solano et al., 2020; Hwang & Chang, 2011).